THE INFLUENCE OF NEW METHODS OF MODERN EDUCATION ON THE FORMATION OF A PERSON’S PERSONALITY - Abdukarimova, Malika (MMIT Proceedings, 2023)
Education plays an important role in human life. Perhaps the whole life of a person consists of acquiring new knowledge. It shapes us as a person in society, for communication, for the exchange of knowledge. Forms in us such qualities as discipline, punctuality, sociability. The development of the system of higher and secondary education requires pedagogical science and practice to study and implement modern technologies and new methods of teaching children and youth. The article also discusses the influence of modern education methods on the formation of a person's personality. Teaching methods are given and all the main methods are considered for a thorough study.